Examining The Relationships Between Negative Reviews, Information Quality, Credibility and Consumer Behavior - Kuan-Yin LEE; Prasana Kumar SAMANTA; Ruo-Ping WU (Communications of International Proceedings, 2022)
The popularity of Internet applications encourages consumers to seek information about products, which influences their purchasing decisions. Negative reviews discourage consumers from purchasing products. Therefore, negative reviews in electronic word-of-mouth are important to examine. The present study proposes to broaden the existing concept of negative reviews based on different factors such as information mediators, information characteristics, and interpersonal strength to understand consumers' buying behavior.
Keywords: Psychosocial distance; Brand equity; Negative word of mouth; Reviewer characteristics